Spontaneous Interface Ion Exchange: Passivating Surface Defects of Perovskite Solar Cells with Enhanced Photovoltage. Issue 38 (25th August 2019) - Li, Zhipeng; Wang, Li; Liu, Ranran; Fan, Yingping; Meng, Hongguang; Shao, Zhipeng; Cui, Guanglei; Pang, Shuping
Abstract: Interface engineering is of great concern in photovoltaic devices. For the solution‐processed perovskite solar cells, the modification of the bottom surface of the perovskite layer is a challenge due to solvent incompatibility. Herein, a Cl‐containing tin‐based electron transport layer; SnO x ‐Cl, is designed to realize an in situ, spontaneous ion‐exchange reaction at the interface of SnO x ‐Cl/MAPbI3 . The interfacial ion rearrangement not only effectively passivates the physical contact defects, but, at the same time, the diffusion of Cl ions in the perovskite film also causes longitudinal grain growth and further reduces the grain boundary density. As a result, an efficiency of 20.32% is achieved with an extremely high open‐circuit voltage of 1.19 V. This versatile design of the underlying carrier transport layer provides a new way to improve the performance of perovskite solar cells and other optoelectronic devices. Abstract : A new method is developed to synthesize SnO x ‐Cl colloids and to realize an in situ and spontaneous ion‐exchange reaction during the perovskite film crystallization process. It is found that such ion exchange can perfectly passivate the interface defects and reduce energy loss at the interface.